2019
DOI: 10.1371/journal.pone.0222826
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach for the analysis of clinician recognition of acute respiratory distress syndrome using electronic health record data

Abstract: ImportanceDespite its efficacy, low tidal volume ventilation (LTVV) remains severely underutilized for patients with acute respiratory distress syndrome (ARDS). Physician under-recognition of ARDS is a significant barrier to LTVV use. We propose a computational method that addresses some of the limitations of the current approaches to automated measurement of whether ARDS is recognized by physicians.ObjectiveTo quantify patient and physician factors affecting physicians’ tidal volume selection and to build a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…This inference is based on our previously developed model of physician recognition of ARDS. Previously, we quantified the impact of patient characteristics on physician recognition of ARDS and subsequent LTVV delivery, by comparing physician behavior with ARDS patients to physician behavior with a novel hypoxemic ‘control’ cohort [ 27 ]. We found that the largest confounding characteristics in both ARDS and control cohorts was patient height (reported as the sex-neutral ‘predicted body weight’).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This inference is based on our previously developed model of physician recognition of ARDS. Previously, we quantified the impact of patient characteristics on physician recognition of ARDS and subsequent LTVV delivery, by comparing physician behavior with ARDS patients to physician behavior with a novel hypoxemic ‘control’ cohort [ 27 ]. We found that the largest confounding characteristics in both ARDS and control cohorts was patient height (reported as the sex-neutral ‘predicted body weight’).…”
Section: Methodsmentioning
confidence: 99%
“…R(h i ): institutional level recognition rates of mild, moderate, or severe patients [ 27 ] (Fig. 2 B).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible to use the traditional quantitative chest CT metrics, such as volume and density to monitor the existence of ARDS. However, to our knowledge, no studies have used quantitative results to monitor the ARDS in COVID-19, while few quantitative results were used in some diagnosis models [14].…”
Section: Ivyspringmentioning
confidence: 99%